2019
DOI: 10.1111/psyg.12416
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent antipsychotic use in older adults treated with antidepressants in Asia

Abstract: Aim Depressive disorders are common in old age. Antipsychotics (APs) are often used as an adjunctive treatment with antidepressants (ADs) in this population but its patterns of use in Asia are not known. This study explored the rate of combination of APs and ADs in older adult psychiatric patients in Asia. Methods This is a secondary analysis of the database of a multicentre study which recorded participants’ basic demographical and clinical data in standardised format in 10 Asian countries and territories. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…Other research foci include psychiatric management patterns (Abdul Khaiyom, Mukhtar, & Oei, 2019; Dong et al, 2019; S.‐C. Park, Oh, et al, 2019; Zhong et al, 2019), electroconvulsive therapy, validations of translated scales (C.‐S.…”
Section: Methodsmentioning
confidence: 99%
“…Other research foci include psychiatric management patterns (Abdul Khaiyom, Mukhtar, & Oei, 2019; Dong et al, 2019; S.‐C. Park, Oh, et al, 2019; Zhong et al, 2019), electroconvulsive therapy, validations of translated scales (C.‐S.…”
Section: Methodsmentioning
confidence: 99%
“…In Japan, 140 out of 229 patients (61.1%) received hypnotics. This rate is the highest among all the countries and areas that participated in the survey (Dong, Zeng, Zhang, Ungvari, Ng, Chiu, et al, 2019).…”
Section: Resultsmentioning
confidence: 96%
“…The DSM‐4 has also been used in countries where the ICD system is not commonly used in clinical practice. The Anatomical Therapeutic Chemical system, developed by the World Health Organization, was used to classify psychotropic drugs prescribed by REAP members (Dong, Zeng, Zhang, Ungvari, Ng, Chiu, et al, 2019; Dong, Zeng, Zhang, Yang, Chen, Najoan, et al, 2019; Dong, Zeng, Zhang, Yang, Chen, Sim, et al, 2019). Each participating country was asked to provide 100–500 prescriptions of patients with schizophrenia, depending on the size of their psychiatric resources.…”
Section: Methodsmentioning
confidence: 99%
“…For example, many people in the central region of China (e.g., Hunan, Hubei, and Jianxi provinces) prefer spicy foods, which could increase the risk of constipation ( 71 ), while those in the eastern region prefer bland foods. The advantage of TCM in terms of remission rate was more obvious in the inpatient group compared to the mixed inpatient and outpatient group, which may be related to better treatment adherence among inpatients ( 72 , 73 ) or due to a small number of studies on mixed patient sample ( n = 2). As expected, meta-regression analysis found that a longer trial duration (β = 0.009, P = 0.013) was associated with a higher remission rate of constipation, probably because the delivery of TCM is more stable in longer studies.…”
Section: Discussionmentioning
confidence: 95%